Global warming and testis function: A challenging crosstalk in an equally challenging environmental scenario - De Toni, Luca; Finocchi, Federica; Jawich, Kenda; Ferlin, Alberto (Frontiers in Cell and Developmental Biology, 2023)
Environmental pollution, accounting for both chemical and physical factors, is a major matter of concern due to its health consequences in both humans and animals. The release of greenhouse gases with the consequent increase in environmental temperature is acknowledged to have a major impact on the health of both animals and humans, in current and future generations. A large amount of evidence reports detrimental effects of acute heat stress on testis function, particularly on the spermatogenetic and steroidogenetic process, in both animal and human models, wich is largely related to the testis placement within the scrotal sac and outside the abdomen, warranting an overall scrotal temperature of 2°C–4°C lower than the core body temperature. This review will provide a thorough evaluation of environmental temperature’s effect on testicular function. In particular, basic concepts of body thermoregulation will be discussed together with available data about the association between testis damage and heat stress exposure. In addition, the possible association between global warming and the secular decline of testis function will be critically evaluated in light of the available epidemiological studies.